Survival differences between heart failure in general practices and in hospitals - Wendelboe Nielsen, O (Copyright 2003 by Heart, 2003)
Objectives: To compare the survival of patients thought to have heart failure in general practice (GP-HF) with that of patients with heart failure in hospital (hospital-HF), patients with heart disease but without heart failure (non-HF), and a control group without heart disease. Design and setting: Cross sectional study from general practice with a prospective follow up from 5.3 to 7.4 years. Participants: 2157 community participants, 1999 of whom lived outside nursing homes, were selected because they were registered with four general practitioners at entry. Study participants were divided into the four groups after a review of general practice case notes, questionnaires, and interviews. Main outcome measures: Five year survival and multivariate predictors of all cause mortality. Results: Five year survival was 76% in the control group (n = 571, mean age at entry 74.1 years), 71% in non-HF patients (n = 218, 74.4 years), 61% in GP-HF patients (n = 67, 75.8 years), and 39% in hospital-HF patients (n = 33, 76.7 years). The median survival times were 6.8 years for GP-HF patients and 3.9 years for hospital-HF patients. Significant predictors of mortality in the multivariate Cox model of 1979 patients living outside nursing homes were hospital-HF (hazard ratio (HR) 2.1, p = 0.002), GP-HF (HR 1.7, p = 0.004), non-HF heart disease (HR 1.4, p = 0.03), previous myocardial infarction (HR 1.6, p = 0.04), no response to questionnaire (HR 2.0, p < 0.0001), higher age (for every 10 years, HR 2.4, p < 0.0001), and male sex (HR 2.1, p < 0.0001). Other factors such as atrial fibrillation, hypertension, and diabetes were not significant. Conclusion: Heart failure in general practice is associated with a worse survival than that seen in the control group but is better than for patients who have been treated at least once for heart failure in a hospital.